The Semiotics of Horror Props in the Film Rambut Kafan and Their Relevance to Theatre Creation - Setia Pribowo; Riana Putra; Mohamad Zaini Alif; Sheila Kurnia Putri (PANTUN: Jurnal Ilmiah Seni Budaya, 2026)
The development of Indonesian horror films over the past decade demonstrates a strong tendency toward the use of visual props as constructors of atmosphere and meaning. The film Rambut Kafan consistently employs long hair, burial shrouds, and ritual objects as key horror signs. This study aims to analyze the semiotic meanings of horror props in Rambut Kafan using Charles Sanders Peirce’s semiotic approach and to explore their potential as inspiration for theatrical artistic creation. The novelty of this research lies in mapping the system of horror prop signs from film into the context of artistic transformation in theater, rather than merely interpreting visual meanings within the film medium. This qualitative research analyzes selected scenes that prominently feature the main horror props. The findings indicate that these props function as icons, indices, and symbols representing death, trauma, and culturally liminal spaces. The practical implications of this study suggest that horror props from film can be transformed into metaphorical, immersive, and multisensory theatrical elements, thereby enriching visual creation strategies in contemporary theater practice.